Annual premium of life in insurance with uniform assumptions - Aprijon Aprijon (Science, Technology, and Communication Journal, 2021)
This Study discusses life insurance for life with a uniform assumption method. The purpose of this study is to calculate the annual premium that must be paid by life insurance participants. This research was conducted at the General Insurance Group company, which is located on the street Arifin Ahmad, Pekanbaru City, Indonesia. To determine the annual life insurance premium, the interest rate and discount factor, initial lifetime annuity, single premium, and the annual premium. After doing the research, the results of the calculation of the annual premium for life insurance for life using uniform assumptions for each participant life insurance are different. The amount of annual life insurance premiums uses a uniform assumption that is smaller than the annual life insurance premiums obtained from insurance companies.